A retórica dos discursos de Lula, Lugo e Cristina Kirchner na 40ª. Cúpula de Chefes de Estado do MERCOSUL - Tateishi, Adriana Akemi (2013)
In the Brazilian city Foz do Iguaçu, region where it can be found the Triple Frontier (Tríplice Fronteira) among Argentina, Brazil and Paraguay, the presidents of these three countries met in December 17th, 2012, together with the Uruguayan president and other Heads of State who were invited for the 40th MERCOSUL Summit. In this context, our objects of study are the speeches given by the Brazilian President Luiz Inácio Lula da Silva, by the Argentinean President Cristina Kirchner and also by Fernando Lugo, the Paraguayan President. The goal is to develop the rhetoric analyses of these discourses and observe how the speakers position themselves in concern of the integration and the MERCOSUL. Therefore, we have the Rhetorical Discourse Theory as basis for the analyses that are going to be divided in the three purposed dimensions for this theory: rationalizing dimension, esthetics dimension and political dimension.